Collaborative Planning and Teaching English Vocabulary with Virtual Reality: A Community Service in SD Gunung Batu Cianjur - Elis Homsini Maolida; Aji Mulyana; Siti Rahma R; Elsa Adetia; Anzalna Rizki (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
This community service is part of a larger project of teachers' and student teachers’ training and focuses group discussion to utilize the technology of virtual reality (VR) in learning English vocabulary in fifteen elementary schools in Cipanas Cianjur. This paper focuses on the implementation of collaborative planning and teaching between a teacher and three student teachers under the supervision of a teacher educator in integrating virtual reality to teach English vocabulary to 41 young learners in SD Gunung Batu. As a result of collaboration on integrating VR in vocabulary teaching, young learners’ vocabulary outcome improved with pre-test mean score was 55.8 and post-test mean score were 95.6. In addition, the teacher and student teachers also show an ability to design lesson plan as well as collaboratively implement it in the classroom.